The rate of patients screened positive for gaming disorder/Internet gaming disorder among adolescents with mental health issues assessed by two screening tests: A nine‐item screening test for GD (GAMES Test) and the Ten‐Item Internet Gaming Disorder Test (IGDT‐10) - Masaru Tateno; Takanobu Matsuzaki; Ayumi Takano; Yukie Tateno; Takahiro A. Kato; Susumu Higuchi (PCN Reports)
Abstract Aim The aim of this study is to estimate the rate of patients who screened positive for gaming disorder (GD) in ICD‐11 among adolescents with psychiatric and/or developmental disorders by using two screening tests: a nine‐item screening test for GD, GAMing Engagement Screening test (GAMES Test), and the Ten‐Item Internet Gaming Disorder Test (IGDT‐10). Methods Subjects were 257 adolescent patients attending a psychiatric clinic in Sapporo, Japan. They were asked to complete two questionnaires. The total score on the IGDT‐10 was calculated by two different scoring methods, original version (OV) and modified version (MV). The three groups were also compared on the basis of their clinical diagnoses. Results Of the 203 respondents, 42 (20.7%) screened positive using the GAMES Test. With respect to the IGDT‐10, only eight (3.9%) screened positive using the IGDT‐10 OV scoring, while 55 (27.1%) screened positive using the IGDT‐10 MV. The most notable finding was that the mean total scores on the GAMES Test and the IGDT‐10 MV were significantly higher in the attention deficit hyperactivity disorder group than in the other two groups (depression and autism spectrum disorder). Conclusion The results of this study showed that adolescents with mental health problems had a higher rate of screening positivity on self‐rated screening tools for GD than the general population. Because excessive gaming has a wide range of adverse effects on adolescents' mental health, early detection of probable GD is crucial. Screening for GD should be part of routine clinical practice.